1983
DOI: 10.3382/ps.0621626
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diet, Bacitracin, and Body Weight Restrictions on the Intestine of Broiler Chicks

Abstract: Six experiments were conducted to evaluate the effects of diet, bacitracin, and body weight restrictions on the intestine of the broiler chick. Bacitracin, at levels of 11 and 55 ppm, significantly increased body weight, significantly reduced small intestine weight, but had no significant effect on liver weight of chicks fed a soybean protein and sucrose-based diet. The greatest effects were observed in the ileum where weight, moisture, length per unit of body weight, and dry matter per unit of length were all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0
3

Year Published

1985
1985
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 16 publications
(22 reference statements)
3
6
0
3
Order By: Relevance
“…Moreover, mucosal weights of the jejunum and duodenum plus jejunum, as well as total intestinal length, were less in the ANTI than in PROBIO group, implicating that these two treatments have different mechanisms of regulatory actions on longitudinal and mucosal growth of the intestine. In addition, compared with CON, the ANTI group exhibited lesser mucosal weights of the duodenum, jejunum and duodenum plus jejunum by 24.0%, 6.5% and 10.3%, respectively, albeit statistically insignificant, which was similar to previous reports (Stutz et al, 1983;Fethiere and Miles, 1987;Veselinova et al, 1987). These results are thus thought to be reflective of the generally accepted concept that antibiotics dampen the mucosal thickening induced by enterotoxigenic microorganisms in the gut, which results in an increase of the proportion of absorbed nutrients utilized for growth of tissues other than the gut usually contributing to enhancement of growth performance (Visek, 1978;Cromwell, 2001).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, mucosal weights of the jejunum and duodenum plus jejunum, as well as total intestinal length, were less in the ANTI than in PROBIO group, implicating that these two treatments have different mechanisms of regulatory actions on longitudinal and mucosal growth of the intestine. In addition, compared with CON, the ANTI group exhibited lesser mucosal weights of the duodenum, jejunum and duodenum plus jejunum by 24.0%, 6.5% and 10.3%, respectively, albeit statistically insignificant, which was similar to previous reports (Stutz et al, 1983;Fethiere and Miles, 1987;Veselinova et al, 1987). These results are thus thought to be reflective of the generally accepted concept that antibiotics dampen the mucosal thickening induced by enterotoxigenic microorganisms in the gut, which results in an increase of the proportion of absorbed nutrients utilized for growth of tissues other than the gut usually contributing to enhancement of growth performance (Visek, 1978;Cromwell, 2001).…”
Section: Discussionsupporting
confidence: 90%
“…All of the 5 antibiotics tested (Experiment 3) resulted in significantly lower intestinal weights. The reduction in intestinal weight observed in this study is in agreement with the results of earlier investigators (Coates et al, 1955;Jukes et al, 1956;Hill et al, 1957;Stutz et al, 1983c). However, the lack of a correlation between the level of dietary antibiotic and intestinal weight is in contrast with the results of Stutz et al (1983 c), who reported that the magnitude of reduction in intestinal weight cor- Oxytetracycline (50) Lincomycin (4) Oxytetracycline (50) Lincomycin (4) Lincomycin (4) Lincomycin (4) Lincomycin (4) Lincomycin (4) Lincomycin (4) Penicillin (50) Oxytetracycline (50) Bambermycin (2) Tylan ( 2 Basal 2 is the control diet used in Experiments 4 to 7.…”
Section: Resultssupporting
confidence: 95%
“…Similar to the previous studies, it was thought that dietary antibiotics and PM powder or extract could not have growth promoter activity when birds were kept under optimal conditions such as the highly digestible diets and clean conditions in this Jang et al: The Plum Products in Diets for Broiler Chicks study. In relative weights of organs, decreased intestinal mucosa weight in the ANT vs. the CON group in our study was similar to the previous reports with birds, in which dietary antibiotics exerted a negative effect on the growth of intestinal mucosa (Stutz et al, 1983;Fethiere and Miles, 1987). The relative weight of thymus in the PME group was significantly higher than that in the CON and ANT groups.…”
Section: Discussionsupporting
confidence: 81%